Economic Masculinity Support and Well-Being of Married Women in Luwero District, Uganda: A Cross-sectional Study - Kankindi, Priscillie; Mawa, Michael; Edaku, Charles (International Journal of Global Health, 2025)
Economic masculinity support is paramount in promoting women’s well-being through numerous ways, including enhancing access to healthcare, education, and financial freedom, hence fostering equitable distribution of household responsibilities. However, studies examining the relationship between economic masculinity support and women’s well-being have not been well established in existing research. This study evaluated the relationship between economic masculinity support and the well-being of married women in Luwero district, Uganda. This Cross-Sectional study was conducted among 382 married women aged 18 to 50 years of age, from selected villages in Luwero district. The outcome variable, well-being, was assessed using the Gender Empowerment Measure (GEM). Data were analyzed using the Pearson correlation coefficient and linear regression to ascertain the relationship between economic masculinity support and the well-being of women. The findings show a moderate positive association between economic masculinity support and women's well-being (r = 0.55, p < 0.0001). Regression analysis indicated that economic masculinity support had a significant predictive influence (β = 0.42, p < 0.01) on women’s well-being, accounting for approximately 30% of the variance in well-being outcomes (Adjusted R² = 0.30). Linking economic masculinity supports improved access to essential resources. These results highlight the crucial role of economic support in enhancing women’s welfare, while also emphasizing the need to address socio-cultural barriers to achieve lasting empowerment. The study underscores the significant role of economic masculinity in promoting married women’s well-being. Transforming economic masculinity into a framework of mutual support is essential for advancing gender equity and safeguarding women’s well-being globally
Keywords: Economic Masculinity Support; Financial Empowerment; Women’s Well-being; Luwero District